AB0473 Immunogenicity of biosimilars for rheumatic diseases: an updated review from regulatory documents and confirmatory clinical trials. (12th June 2018) - Strand, V.; Goncalves, J.; Hickling, T.P.; Jones, H.; Marshall, L.; Isaacs, J.
Abstract : Background: Several biosimilars have been approved for the treatment of rheumatic diseases by the European Medicines Agency (EMA) or the US Food and Drug Administration (FDA). Objectives: To summarise immunogenicity data from regulatory documents or confirmatory trials of biosimilars approved by the EMA or FDA for the treatment of rheumatic diseases. Methods: EMA Public Assessment Reports (EPARs), FDA Clinical Summaries, PubMed records, and EULAR and ACR abstracts were searched for immunogenicity data from confirmatory trials of approved TNFα or CD20 inhibitor biosimilars in patients with rheumatic diseases. Data collected included the proportion (%) of patients positive for anti-drug antibodies (ADAbs) among all patients and the proportion (%) of patients with neutralising antibodies (nAbs) among ADAb-positive patients. Results: We identified 10 biosimilars approved by the EMA or FDA: three each for adalimumab (BI 695501, SB5, and ABP 501) and infliximab (SB2, CT-P13, and infliximab-qbtx) and two each for etanercept (GP2015 and SB4) and rituximab (CT-P10 and GP2013). The duration of treatment periods in the 16 identified trials (which varied in design and methodology of ADAb/nAb detection) ranged from 12 weeks to 102 weeks. Across treatment groups in all trials, 0% to 62% of patients were ADAb-positive, of whom 0% to 100% were also nAb-positive. The lowest proportions of ADAb-positive (0%–13%) and nAb-positive patients (0%–3%) were observed in the trials of etanercept and its biosimilars, and the highest in the trials of infliximab and its biosimilars (ADAbs: 20%–62%; nAbs: 88%–100%). Consistent with the biosimilar designation, the proportions of ADAb- and nAb-positive patients in individual trials were similar between the originator and biosimilar products. Of note, in a 52 week trial of etanercept and its biosimilar SB4, the incidence of ADAs by Week 52 was significantly lower with SB4 than with etanercept (1% [3/299] vs 13% [39/296], p<0.001). However, as noted in the SB4 EPAR, this difference, which was not reflected in the incidence of nAbs and efficacy or safety of etanercept, may have been due to an ADAb assay bias in samples collected at Weeks 4 and 8, when 37/39 ADAbs in the etanercept group and 2/3 in the SB4 group were detected. Conclusions: Immunogenicity of the approved biosimilars is generally similar to that of originator products. For ETN, which has been associated with relatively low ADAb levels, there was a discrepancy in ADAb incidence compared with its biosimilar SB4, but those differences were transient and did not affect clinical activity or safety. Acknowledgements: Sponsored by Pfizer Inc. Disclosure of Interest: V. Strand Consultant for: AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Celltrion, Corrona, Crescendo, EMD Serono, Genentech/Roche, GSK, Janssen, Eli Lilly, Merck, Novartis, Pfizer, Regeneron, Samsung, Sandoz, Sanofi, and UCB, J. Goncalves: None declared, T. Hickling Shareholder of: Pfizer, Employee of: Pfizer, H. Jones Shareholder of: Pfizer, Employee of: Pfizer, L. Marshall Shareholder of: Pfizer, Employee of: Pfizer, J. Isaacs Grant/research support from: Pfizer, Roche, Consultant for: Pfizer, Abbvie, Janssen, Roche, Speakers bureau: Pfizer, Abbvie, Roche